Language Evolution in Bookish Social Media: A Netspeak Analysis of Booktok and Bookstagram - Toisuta, Emanuela Giovanni (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2024)
This study investigates the evolution of language on Bookstagram and BookTok using digital ethnography to analyze posts from popular content creators. By employing content and thematic analysis, the research examines how Netspeak, consist of acronyms, emoticons, and abbreviations, reflects online language and identity. The findings reveal that #Bookstagram prefers emojis and a formal, literary style, while #BookTok adopts unique linguistic traits such as symbols and a lack of punctuation, reflecting a more conversational tone. These differences highlight the role of Netspeak in encouraging interaction, sharing literary experiences, and building a sense of community in online book discussions. The study shows the impact of internet culture on communication practices, illustrating the dynamics of identity and community in digital spaces. Ethical clearance was obtained, and permissions were secured from content creators, ensuring compliance with ethical standards and respect for intellectual property rights. This research provides valuable insights into how digital spaces shape language use and community building within online book communities.